STRUCTURE–ACTIVITY RELATIONSHIPS FOR A SERIES OF PHENYL (MORPHOLINO) METHANETHIONE DERIVATIVES: CYTOTOXICITY AGAINST ARTEMIA SALINA AND CANCER CELL LINES. - AGNIMONHAN, Finagnon H.; GLINMA, BIENVENU; Ahoussi, Léon A.; Kpoviessi, D. S. Salomé; ACCROMBESSI, COFFI GEORGES; Gbaguidi, A.Fernand (My University, 2020)
A series of phenyl (morpholino) methanethione derivatives (a-h) has been evaluated for antiproliferative activity vitro against MCF-7 and HCT-116 cancer cells by the MTT assay and toxicity on the larvae of Artemia salina Leach. From the toxicity studies and structural activity relationship of compounds (a-h), it is clear that mesomeric donor effect groups on benzene ring have increased actively this toxicity. Moreover, for cytotoxicity studies on MCF-7 and HCT-116 cancer cells in breast and colon cancer respectively, the compounds (a) and (f) have showed an interesting activity with 100 μM of (f) on MCF-7 cells (35.7 ± 3.1%) and 100 μM of the compound (a) on the HCT-116 cells (58.1 ± 1.5%). A cytotoxicity on MCF-7 of these compounds has expressed a toxicity on the larvae of Artemia salina. This does phenyl (morpholino) methanethione derivatives a potential source of anticancer molecules.
Keywords: Artemia salina Leach; MCF-7; HTC-116; phenyl (morpholino) methanethione; derivatives.